فاعلية استخدام الوسائط المتعددة في تطوير خطط اللعب الدفاعية للاعبي كرة القدم - ميم المختار (Journal of Sport Science Technology and Physical Activities, 2025)
Technology plays a principal role in providing sources teaching and training,the computer is one of these important technological tools used in this domain it corrects the mistakes of each player and contribute in simplifying the training programmes and like this we can gain time and helps in the development of training processus. Unfortumately i discovered that the audiovisual tools are mot used in training,this is what i noticed in my theoric experience,from searchers opinions and experts of algerian football. This is way the searcher determine that the results of his research are reconizing the effect of using technological tools in scientific analyses in the amelioration and developmnt of tactic defensive of footballers